Pelatihan Pembuatan Video Pembelajaran Dengan Mengimplementasikan Teori Filler Bagi Guru Guru Muda - Armilia Riza; Rika Afriyanti; Hevriani Sevrika (STKIP PGRI Sumatera Barat, 2021)
Online learning is one way to overcome problem in education field during covit 19 out break. Facing this defiance condition, teachers are demanded more creative in presenting course by adapting learning model which is more interesting and fun. Team of English lecturers of STKIP PGRI Sumatera Barat bridge this condition by having devotion to the community. This activity is as an effort to improve teachers’ communication technique especially to young teachers in presenting their course more interesting by applying fillers theory. Young teachers in SMP Nasional as one of private school are encouraged by applying fillers technique which is applied via the teaching video using the kine master application. Fillers used that are effective in class communication and teaching videos are two the most important things put in this program. Young teachers are the main target in this program since team feels that they still have lack of experiences and teaching time. The team hopes the equipped with the various fillers techniques in constructing various teaching video, their video results will be much better and interesting for students.